Re-Understanding the Problem of Induction in Empirical Science - Rumiari, Rumiari; Hardika, Hardika; Ahmad, Ahmad (International Journal of Multi Discipline Science (IJ-MDS), 2024)
A problem is a statement or truth based on experience that is used as a hypothesis. In formulating a hypothesis based on statements as an inductive way of thinking. The problem of induction can also be formulated as a question about the validity or truth of universal statements based on experience. Thinking based on logic gives humans the possibility to gain knowledge, which is deeper than the meaning of what is thought. In formulating a hypothesis based on statements as an inductive way of thinking. The problem of induction can also be formulated as a question about the validity or truth of universal statements based on experience. In the case of inductive logic, however, these relationships vary in strength, measures of conditional probability reflect the degree of rational confidence that a person should have in the hypothesis that empirical science should be so characterized by its methods. With this method, we deal with science with a system based on what we do to what is done. The difference between the psychological view of knowledge which is related to empirical facts, and the logic of knowledge which is only related to empirical facts. With logical connections, the belief in inductive logic is largely due to confusion between psychological problems and epistemological problems.